Analysis of transcriptional activity by the Myt1 and Myt1l transcription factors. Issue 6 (9th March 2018) - Manukyan, Arkadi; Kowalczyk, Izabela; Melhuish, Tiffany A.; Lemiesz, Agata; Wotton, David
Abstract: Myt1 and Myt1l (Myelin transcription factor 1, and Myt1‐like) are members of a small family of closely related zinc finger transcription factors, characterized by two clusters of C2HC zinc fingers. Both are widely expressed during early embryogenesis, but are largely restricted to expression within the brain in the adult. Myt1l, as part of a three transcription factor mix, can reprogram fibroblasts to neurons and plays a role in maintaining neuronal identity. Previous analyses have indicated roles in both transcriptional activation and repression and suggested that Myt1 and Myt1l may have opposing functions in gene expression. We show that when targeted to DNA via multiple copies of the consensus Myt1/Myt1l binding site Myt1 represses transcription, whereas Myt1l activates. By targeting via a heterologous DNA binding domain we mapped an activation function in Myt1l to an amino‐terminal region that is poorly conserved in Myt1. However, genome wide analyses of the effects of Myt1 and Myt1l expression in a glioblastoma cell line suggest that the two proteins have largely similar effects on endogenous gene expression. Transcriptional repression is likely mediated by binding to DNA via the known consensus site, whereas this site is not associated with the transcriptional start sites of genes with higher expression in the presence of Myt1 or Myt1l. This work suggests that these two proteins function similarly, despite differences observed in analyses based on synthetic reporter constructs. Abstract : We show that Myt1 and Myt1l regulate a very similar set of genes, despite having different transcriptional activities when assayed on synthetic reporters. Transcriptional repression by Myt1 and Myt1l appears to be mediated via their canonical binding site, whereas this site is not significantly associated with genes that have higher expression in the presence of Myt1 or Myt1l.